2001
DOI: 10.1136/bmj.322.7291.889
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and childhood onset type 1 diabetes: population based cohort study

Abstract: The work of McCarron et al has provided clear evidence that substantial changes in blood pressure levels can occur, and both these and other data suggest that such changes can occur in broad population groups. New epidemiological studies that provide reliable information about the most likely causes of these changes, and new large scale randomised trials that identify effective means of changing population levels of blood pressure, are needed. To have the greatest impact on the global burden of cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
136
11
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(166 citation statements)
references
References 31 publications
15
136
11
4
Order By: Relevance
“…MPH = SDS birth length or height−SDS MPH Diff., difference from study, care was taken to obtain the birth length and birthweight data from the growth curves maintained for each child by the Child Health Services. Several epidemiological studies have reported that type 1 diabetic children have a higher birthweight [10][11][12][13]. This was not observed in the present group of children developing diabetes before 6 years of age.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…MPH = SDS birth length or height−SDS MPH Diff., difference from study, care was taken to obtain the birth length and birthweight data from the growth curves maintained for each child by the Child Health Services. Several epidemiological studies have reported that type 1 diabetic children have a higher birthweight [10][11][12][13]. This was not observed in the present group of children developing diabetes before 6 years of age.…”
Section: Discussioncontrasting
confidence: 69%
“…High birthweight has been reported as a risk factor for type 1 diabetes [10][11][12][13]. We have demonstrated that children born with type 1 diabetes high-risk HLA genotypes had an increased risk of high birthweight corrected for gestational age (i.e.…”
Section: Introductionmentioning
confidence: 83%
“…The associations, however, are somewhat contrary to expectations. Although the effects are relatively weak, high birthweight and increased childhood growth rates are postulated to increase the risk of type 1 diabetes [37][38][39]. Yet, despite their high birthweight and increased BMI during childhood, children of mothers with type 1 diabetes have a lower risk of type 1 diabetes than children of fathers with type 1 diabetes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Children born large for gestational age (LGA) had a higher risk of type 1 diabetes later in childhood [15]. In one study the incidence of type 1 diabetes was found to increase almost linearly with birthweight (BW) [16].…”
Section: Introductionmentioning
confidence: 99%
“…LGA and other altered growth rates appear to be associated with type 1 diabetes risk [15,16,[23][24][25][26]. It is not clear whether islet autoantibodies are associated with LGA or growth, or whether the relationship between high BW and type 1 diabetes is a result of the same genes being associated with both increased risk for type 1 diabetes and high BW.…”
Section: Introductionmentioning
confidence: 99%